Incidence, consequences, and predictors of serious chemotherapy‐induced thrombocytopenia in nasopharyngeal carcinoma - Lu‐Lu Zhang; Xi Chen; Ying‐Ying Huang; Chi‐Xiong Liang; Meng‐Yun Qiang; Zhuo‐Chen Cai; Ze‐Jiang Zhan; Ying Deng; Jia‐Yu Zhou; Hao‐Yang Huang; Xiang Guo; Xing Lv (Cancer Medicine, 2023)
Abstract Objectives This study aimed to investigate the incidence, consequences, and predictors of serious chemotherapy‐induced thrombocytopenia (CIT) in nasopharyngeal carcinoma (NPC). Materials and Methods We retrospectively reviewed the clinical records of patients with NPC between 2013 and 2015. Multivariate Cox proportional hazards regression model and propensity score matching were used to estimate the effect of serious CIT on overall survival. Univariate and multivariate logistic regression analyses were applied to identify the predictors of serious CIT. Results and Conclusion The incidence of serious CIT was 5.21% in patients with NPC. Patients who experienced serious thrombocytopenia had a worse long‐term prognosis, while the difference in short‐term survival rate was slight. Chemotherapy regimens of gemcitabine and platinum, 5‐fluorouracil and platinum, taxane and platinum, serum potassium ion concentration, serum lactate dehydrogenase levels, platelet count, red blood cell count, and estimated glomerular filtration rate were predictors of serious CIT.